Strengthening the National Framework for Climate Services in Mali - Diallo, Aboubacar; Diarra, Afoussatou; Dossou-Yovo, Elliott Ronald (2025)
The National Framework for Climate Services (NFCS) is a strategic initiative under the Global Framework for Climate Services (GFCS) designed to strengthen the delivery of user-relevant climate information to support adaptation, resilience, and informed decision-making across sectors such as agriculture, water management, and disaster risk reduction. In Mali, the NFCS was officially established and launched in October 2023 under the leadership of Mali-Météo, in collaboration with key national authorities and institutions. Despite its establishment, the NFCS faced several limitations, including low awareness among policymakers and stakeholders regarding the importance of climate information, insufficient integration of climate data into national planning and development strategies, limited coordination among institutions, and inadequate mechanisms for effective dissemination of climate information to end-users. To address these gaps, the AICCRA project in Mali implemented a series of participatory activities from 2022 to 2025, aimed at strengthening the NFCS. These included capacity-building sessions on digital platforms such as Maproom, ENACTS, and AgData Hub, training on innovative CIS dissemination channels tailored to farmers’ preferences (e.g., WhatsApp, SMS, phone calls, radio, and TV), and multi-sectoral workshops to enhance coordination and awareness. The outcomes of these interventions were significant: enhanced technical capacity of NFCS members, improved institutional coordination and data sharing, increased awareness and uptake of CIS among policymakers and local stakeholders, better accessibility and timely dissemination of climate information, and strengthened evidence-based decision-making and policy integration. Based on these outcomes, recommendations were formulated to sustain and consolidate the NFCS, including institutionalizing regular capacity-building programs, enhancing multi-sectoral coordination, scaling up CIS dissemination at local levels, integrating CIS into policy and planning frameworks, strengthening digital platforms and data accessibility, promoting long-term sustainability and resource mobilization, and establishing monitoring and evaluation mechanisms to track CIS uptake and impact. Collectively, these efforts provide a robust foundation for the NFCS in Mali to support informed decision-making and enhance climate resilience across key sectors.